The viscosity and surface tension of supercooled levitated droplets determined by excitation of shape oscillations - Singh, Mohit; Jones, Stephanie Helen; Kiselev, Alexei; Duft, Denis; Leisner, Thomas (Atmospheric measurement techniques, 2023)
We report a new method for determining the viscosity and surface tension of supercooled liquid droplets using electrodynamic levitation and phase analysis of shape oscillations. The method uses a high-frequency alternating electrical potential to excite shape oscillations in a levitated droplet, and the phase shift in the oscillations is used to simultaneously determine droplet viscosity and surface tension. The advantages over existing contactless methods include its applicability to atmospherically relevant temperatures and the possibility of continuously monitoring changes in real time. We demonstrate proof-of-concept measurement for supercooled water droplets and dilute sucrose solution droplets, and we anticipate that the technique could be used to measure viscosity values for droplets containing dilute organics. The technique is especially well-suited for investigation of the role of atmospheric processing in the viscosity and surface tension of solution droplets in equilibrium with a given or changing relative humidity.
Gesehen am 12.07.2024